Comparison of Lecture and Puzzle for Teaching Medical Emergency to Anesthesiology Students: Students’ Learning and Viewpoints - Maliheh sadeghnezhad forotagheh; Maryam bagheri (مجله ایرانی آموزش در علوم پزشکی, 2013)
Introduction: Emphasis on active learning in training leads to the development of new educational strategies for teaching theoretical and clinical courses in medical sciences. Active involvement in the teaching-learning process improves learning. The purpose of the present study is to compare two methods of lecturing and puzzle in Medical Emergency Course, regarding students’ learning & viewpoints. Methods: In this quasi-experimental study with pre-and post-test design, 60 Anesthesiology students enrolled in medical emergency course in Paramedics College of Mashhad Islamic Azad University, participated. By census sampling, students were non-randomly assigned to two groups of 30. In one, participants were trained through lecturing and in the other through puzzle. Each session began with a pre-test, and after teaching, post-test was taken. At the end of the program, students’ viewpoints on the teaching method were surveyed using a researcher-made questionnaire. Data were analyzed by SPSS using statistical tests of paired t-test, independent t-test, and chi square. Results: Mean of student pre-test scores (out of 10) in the puzzle group was 4.1±1.35 & in the lecture group was 4.4±1.25, which were not significantly different. Mean of students’ post-test scores in the puzzle & lecture groups were 7±1.47 & 8.5±1.1 respectively, which were significantly different. In the puzzle group, learning improved more than the lecture group. Also the survey showed more satisfaction in the puzzle group, according to more student participation, motivating them about lesson topics, fostering effective peer relationships, and deep learning. Conclusion: Considering the favorable effects of the puzzle method on learning and satisfaction of students, it is suggested that this teaching method be applied for teaching courses of medical sciences.